Reassessing Payment Methods in E-Commerce: Why Consumers Prefer Cash on Delivery - Nasution, Muhammad Dharma Tuah Putra; Surya, Dwi Hadi (Talenta Publisher, 2025)
This study investigates the determinants of Cash on Delivery (COD) adoption in e-commerce through the lens of the Theory of Planned Behavior (TPB). Specifically, it examines the roles of perceived convenience, prior experience, and perceived security in shaping consumer behavior. COD remains a critical payment method in emerging markets where digital infrastructure is limited, and trust in online payment systems is low. The study proposes a quantitative framework involving a sample of 563 e-commerce users to test the hypothesized relationships. Measurement items are adapted from established scales, and Partial Least Squares Structural Equation Modeling (PLS-SEM) will be employed for data analysis. The anticipated findings are expected to contribute to consumer behavior literature by offering insights into the psychological and practical drivers of COD adoption. Furthermore, the study aims to provide actionable recommendations for e-commerce platforms to optimize payment strategies in trust-deficient environments.